ID: 49. Issue 1 (November 2015) - Zhou, Peng; Boyd, Victoria; Tachedjian, Mary; Cui, Jie; Smith, Ina; Cowled, Chris; Wynne, James; Wang, Linfa; Baker, Michelle
<x xml:space="preserve">Abstract</x> Bats are known to harbour a number of emerging and re-emerging zoonotic viruses, many of which are highly pathogenic in other mammals (MERS, Ebola among others) but result in no clinical symptoms in bats. The ability of bats to coexist with viruses may be the result of rapid control of viral replication early in the immune response. To determine the role of IFNs in the ability of bats to coexist with viruses we sequenced the type I IFN locus of the Australian black flying fox, Pteropus alecto, providing the first map of the IFN region of any bat. Our results reveal a highly contracted type I IFN family consisting of only ten IFNs, including three functional IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rk7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> loci. Furthermore, the three IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rk7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>s are constitutively expressed in unstimulated bat tissues and cells and their expression is unaffected by viral infection. Analysis of the putative promoter regions of the bat IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rk7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> genes has revealed that the three IRF binding modules are different in the identified bat IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rk7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>, which may contribute to its constitutive expression. These discoveries are consistent with differences in the IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rk7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> system of bats compared with other mammals and may have important implications for the role of type I IFNs in the ability of bats to coexist with viruses.